The Electrochemical Stability of Starch Carbon as an Important Property in the Construction of a Lithium-Ion Cell - Beata Kurc; Marita Pigłowska; Łukasz Rymaniak (Entropy, 2021)
This paper shows use of starch-based carbon (CSC) and graphene as the anode electrode for lithium-ion cell. To describe electrochemical stability of the half-cell system and kinetic parameters of charging process in different temperatures, electrochemical impedance spectroscopy (EIS) measurement was adopted. It has been shown that smaller resistances are observed for CSC. Additionally, Bode plots show high electrochemical stability at higher temperatures. The activation energy for the SEI (solid–electrolyte interface) layer, charge transfer, and electrolyte were in the ranges of 24.06–25.33, 68.18–118.55, and 13.84–15.22 kJ mol−1, respectively. Moreover, the activation energy of most processes is smaller for CSC, which means that this electrode could serve as an eco-friendly biodegradable lithium-ion cell element.